2013
DOI: 10.2355/isijinternational.53.818
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Solidification Temperature of SiO2–CaO–Na2O Melts for Fluorine Free Mould Flux

Abstract: Fluorine-free mould flux has been required to reduce corrosion of continuous casters. In this paper, Na2Ca2Si3O9 has been applied to an alternative crystalline phase of Ca4Si2O7F2 (cuspidine) that crystallized in commercial flux films. Effects of basicity described as T.CaO/SiO2 and additions of Li2O, Na2O, MgO and/or MnO into Na2Ca2Si3O9 composition mould flux on viscosity and solidification temperature were studied and the solidified specimens were examined by X-ray diffraction to identified crystalline phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Lu et al, 14) have investigated the influence of Na 2 CO 3 on properties of low fluoride content mold flux, and the results showed that the viscosity and viscous activation energy decreased obviously when the Na 2 CO 3 content increased. Takahira et al, 15) found that the viscosity of fluorine free mold flux reduced with the increase of basicity. Also, the research of Arefpour et al, 16) suggested that all of the B 2 O 3 , Li 2 O, TiO 2 , Fe 2 O 3 , ZnO, and Na 2 O can lower the viscosity of mold flux.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al, 14) have investigated the influence of Na 2 CO 3 on properties of low fluoride content mold flux, and the results showed that the viscosity and viscous activation energy decreased obviously when the Na 2 CO 3 content increased. Takahira et al, 15) found that the viscosity of fluorine free mold flux reduced with the increase of basicity. Also, the research of Arefpour et al, 16) suggested that all of the B 2 O 3 , Li 2 O, TiO 2 , Fe 2 O 3 , ZnO, and Na 2 O can lower the viscosity of mold flux.…”
Section: Introductionmentioning
confidence: 99%
“…21) In fact, during recent years the oscillating cylinder and plate methods were successfully applied for the determination of the steel and slag viscosity at high temperatures (≤ 1 600°C). 4,19,20,22,23) The present study was performed to experimentally investigate an applicability of the vibrating finger viscometer for the measurements of slag viscosity up to 1 600°C and to discuss the high temperature calibration errors such as deviations in geometry of the crucible, the slag stability, the fluid flow, the atmospheric conditions, as well as the difference in both measurement principles. For this purpose CaO-Al 2 O 3 , CaO-SiO 2 binary systems and an CaO-SiO 2 -Al 2 O 3 -MgO industrial blast furnace slag and a glass as a reference system were chosen.…”
Section: Viscosity Measurement Of Slags Using Rotating Bob and Vibratmentioning
confidence: 99%
“…A few other studies were reported to use the different types of viscometers such as the rotation crucible viscometer and the oscillating plate method. [17][18][19][20] The concentric cylinder method was primary used for the determination of slag viscosity. It…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] However, recently published paper from Q. Wang and K. C. Mills 16) pointed out that those fluorine free mold fluxes containing TiO2 have the risk to increase the rate of breakout due to the possible formation of high melting point Ti(C, N) and CaTiO4 that tends to deteriorate the heat transfer behavior in the mold. (2) Using oxides like Na2O, K2O, Li2O, MgO, MnO, B2O3, BaO and rare earth elements oxides to modify the negative effects of the mold flux properties caused by the absence of fluorides; [17][18][19][20][21][22] however, there is no specific crystalline phase, which shows similar properties as cuspidine, has been reported.…”
Section: Introductionmentioning
confidence: 99%